Measuring the value of MRI: Comparative effectiveness & outcomes research - Kang, Stella K. (Journal of magnetic resonance imaging, 2019)
Magnetic resonance imaging (MRI) now provides diagnostic assessment for numerous clinical indications, including lesion detection, characterization, functional assessment, and response to treatment. To maximize the potential to improve health through the use of MRI, it is critical to investigate the impact of MRI on outcomes, and to compare the effectiveness of MRI with existing standard diagnostic approaches. Outcomes of MRI can include survival but also intermediate steps such as potential reduction in unnecessary therapy, shorter time to the appropriate therapy, or shorter periods of hospital admission. To understand the effectiveness of an imaging test's sensitivity and specificity, the results' consequences are weighed, reflecting the disease type, severity, and treatment effects. In some instances, other modalities may be faster, more readily available, or less costly than MRI but additional disease‐related information or better accuracy may translate to greater population level benefit. For health policy decisions and clinical guidelines, studies of comparative outcomes can lend depth to the strength of the evidence, the specific benefits vs. harms of using one test over another, and the most effective use of the test in terms of target population. Cost effectiveness then allows for a direct comparison of approaches in terms of the cost for the projected gain in life expectancy and/or quality adjusted life expectancy. Expanding the literature on improved efficiency, accessibility, clinical effectiveness, and cost effectiveness will support the directive for better quality and value in healthcare. Level of Evidence 5 Technical Efficacy Stage 5 J. Magn. Reson. Imaging 2019.